Effects and laws analysis for the mining technique of grouting into the overburden bedding separation - Wang, Jian; Ma, Jun; Yang, Keming; Yao, Shuyi; Shi, Xiaoyu (Journal of cleaner production, 2021)
The drastic surface displacement and deformation caused by underground mining will have a serious impact on the ecological environment and the personal and property safety, although a broad range of backfill mining techniques has been applied to practical engineering, there is still a lack of effective methods to analyze the effects and laws of these techniques. In this paper, an analysis method for the effects of the mining technique of grouting into the overburden bedding separation (hereafter also referred to as the GOBS) is proposed, this method can be extended to other types of backfill mining techniques as well, and detailed analysis for a grouting mining district in Huaibei mining area, China was carried out by this method. Subsequently, the characteristics of surface subsidence and deformation (hereafter also referred to as the SSD) were summarized, and the relationship between six representative reduction rates of SSD and injection-extraction ratio were investigated, then the modeling verification and analysis were performed. Finally, the advantages and drawbacks of the mining technique of GOBS and other commonly used mining techniques for reduction SSD are compared. The results demonstrate that the mining technique of GOBS is of high cost-effectiveness to reduce the SSD, meanwhile, the reduction rates of SSD with injection-extraction ratio are subject to the Gompertz model very well, and consistent with actual situations. Therefore, they can be used for the design of grouting working faces and the prediction of SSD, and providing a scientific basis for guiding practical mining working in a safe, efficient and clean way. •Present an analysis method for the effects of the backfill mining techniques.•Process details of the proposed analysis method were elaborated with practical engineering.•The characteristics of surface subsidence and deformation were summarized.•Reduction effects of surface subsidence and deformation concerning injection-extraction ratio obey Gompertz model.•The advantages and drawbacks of several mining techniques for reduction deformation are compared.